Between Ideology and Utopia: Re-thinking Conflict and Reconciliation in Psychotherapy (Existential Analysis: Journal of the Society for Existential Analysis, 2005)
Conflict is a recurring theme in psychotherapy much as it is in everyday life. In this paper, I seek to introduce the reader to Ricoeur's work on ideology and utopia and suggest that this might form an alternative, though not exclusive, narrative framework (or critical hermeneutic) for understanding interpersonal conflict and reconciliation. Ricoeur's work on ideology and utopia is unusual for a number of reasons. In particular, it is one of the few attempts to conceptually draw ideology and utopia together within a common framework and develop a social theory where man remain centre-stage and not resigned to being nothing more than a pawn of prevailing economic forces. Drawing on this conceptual foundation, I argue that the interpersonal conflict we encounter between clients might best be resolved by engaging such clients in utopian imaginings and the active re-construction of narrative identities for self and other.
Keywords: conflict; reconciliation; ideology; utopia; Ricoeur